Statistical analysis plan for the 'Rapid Intervention with Glyceryl trinitrate in Hypertensive stroke Trial-2 (RIGHT-2)'. (June 2018) - Scutt, Polly; Appleton, Jason P; Dixon, Mark; Woodhouse, Lisa J; Sprigg, Nikola; Wardlaw, Joanna M; Montgomery, Alan A; Pocock, Stuart; Bath, Philip M
Rationale: Glyceryl trinitrate, a nitric oxide donor, is a candidate treatment for acute stroke; it lowers blood pressure, does not alter cerebral blood flow or platelet function and is neuroprotective in experimental stroke. The ongoing rapid intervention with glyceryl trinitrate in hypertensive stroke trial-2 trial aims to assess the safety and efficacy of paramedic-delivered glyceryl trinitrate in patients with ultra-acute stroke. Aims and design: The rapid intervention with glyceryl trinitrate in hypertensive stroke trial-2 trial is a multicentre UK-based prospective randomised sham-controlled outcome-blinded parallel-group trial in patients with presumed stroke who present to the ambulance service following a 999 emergency call. The primary outcome is the modified Rankin scale measured by central telephone follow-up at 90 days. Results: This paper describes the statistical analysis plan for the rapid intervention with glyceryl trinitrate in hypertensive stroke trial-2 trial and was developed prior to unblinding to treatment allocation. The statistical analysis plan includes details of methods for analyses and unpopulated tables and figures to be included in the primary and other secondary publications. Discussion: Statistical analysis plan details what analyses will be done prior to unblinding to treatment allocation to avoid bias in the findings. Rapid intervention with glyceryl trinitrate in hypertensive stroke trial-2 trial will determine whether glyceryl trinitrate administered ultra-acutely can improve outcome after stroke. The rapid intervention with glyceryl trinitrate in hypertensive stroke trial-2 trial is registered as ISRCTN26986053.